Avaliação da eficiência e do desaguamento de lodo de ETA em Leito de Drenagem utilizando diferentes geotêxteis e aplicação de polímero - Ortiz, Isabela Gagliardi (2022)
During the stages involved in the water treatment process, sludge is formed, which is characterized as solid waste and, therefore, its destination must be compatible with the guidelines of the PNRS - Law 12.305/2010, prioritizing reduction, reuse and recycling. In this sense, dewatering, understood as a method of reducing the volume of sludge, meets the requirements established by the National Policy on Solid Waste. Dewatering is characterized by the removal of free water, supernatant found in the interstices of solids, using natural or mechanical systems. Drainage beds, designated as DB and previously conceptualized as drying beds, are among these natural systems. This technique has shown to be interesting, despite the lack of research using polymers as conditioning. Several authors defend the theory that the WTP sludge does not need a polymer to be dewatered, as it already has chemical conditioners, introduced in the water treatment process, which would facilitate dewatering. Thus, the main objective of this research was to study the application of polymers as a conditioner in the WTP sludge applied to the DB, with a view to improving efficiency and dewatering. For this purpose, a bench scale Drainage Bed system was used, with a total of 108 drainages, including tests without polymer (SP) and with polymer (CP), with 4 geosynthetics (3 non-woven geotextiles and a woven geotextile ), a fixed total solids (ST) content of the sludge of 2% and 3 sludge layer heights (H10, H30 and H50 cm). Subsequently, in order to choose the polymer to be applied to the DBs, cone tests were carried out with different types of polymers, concentrations and dosages, with the respective geotextiles. These results were applied to the BD system, characterized as CP-cone for each geotextile tested. In order to study another polymer selection method, the BD system itself was used, since the TAS (Solid Application Rate) between these two methods were considered different. Thus, tests were performed, characterized as CP-alternative, using the same geotextiles. The analysis of the results highlighted that the CP - alternative tests were able to increase the removal rates, mainly for higher hydraulic loads, with TAS > 6 kg/m2 , with superior quality of drains for all hydraulic loads; the alternative method would be the most indicated because it presented high removal with satisfactory quality. Only the non-woven geotextile GTNT600 showed no statistical difference in dry retained mass regardless of the hydraulic load and the method applied for polymer selection. Regarding the efficiencies, the EF (%) was > 98% for the CP tests. For the ESST (%) the values were > 96%. Higher hydraulic loads obtained higher TSS removal efficiencies, regardless of the test configuration (SP and CP – cone and alternative) with values above 98%.